Adjuvant pelvic irradiation in patients with pathologic T2b carcinoma of the uterine cervix. Issue 2 (1st March 2002) - Uno, T; Ito, H; Itami, J; Sato, T; Minoura, S; Yasuda, S; Aruga, T; Isobe, K; Shigematsu, N; Kubo, A
Abstract : Patients with cervical cancer are subject to postoperative adjuvant therapy if the histopathologic examination reveals parametrial involvement. This study evaluated the patterns of failure in patients with pathologic parametrial invasion (pT2b) treated with adjuvant pelvic irradiation. Between April 1985 and March 1997, 45 patients with pT2b cervical cancer were treated with postoperative pelvic irradiation. The median age was 52 years. Preoperative clinical stages were stage Ib in 8 patients, IIa in 4, and IIb in 33. Twenty-three patients had lymph node metastasis. The median total dose of whole pelvic radiation therapy was 50 Gy. Occurrence of pelvic failure or distant metastasis according to the nodal status was examined. None of the 22 patients without lymph node metastasis developed distant metastasis. Among the 23 node-positive patients, 6 developed distant metastasis as an initial failure site. The 5-year overall survival of the entire group was 78%. The actuarial distant metastasis-free rates at 5 years were 73% and 100% for those with and without pelvic lymph node metastasis, respectively ( P = 0.016). Results support previous evidence for chemoradiation in patients with pelvic lymph node metastasis. However, it appears that the role of systemic chemotherapy for node-negative pT2b patients is yet to be established.